2017
DOI: 10.1016/j.ceb.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the origin, development, and differentiation of hematopoietic stem cells

Abstract: This review chronicles the fate of the hematopoietic cells emerging from the mesoderm that subsequently develops into the adult blood lineages. Specifically, we explain classic techniques utilized in lineage tracing for the hematopoietic system, as well as novel state-of-the-art methods to elucidate clonal hematopoiesis and cell fate mapping at a single-cell level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Our study found the same outcomes in IgAN. As we all know, platelets and lymphocytes are derived from the same hematopoietic stem cells and the PLR should be kept constant for homeostasis [ 28 , 29 ]. Higher PLR condition means relatively high platelets and low lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found the same outcomes in IgAN. As we all know, platelets and lymphocytes are derived from the same hematopoietic stem cells and the PLR should be kept constant for homeostasis [ 28 , 29 ]. Higher PLR condition means relatively high platelets and low lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For hematopoiesis, HSCs are generated in different organs, including the aorta-gonad-mesonephros (AGM), fetal liver and bone marrow. HSCs at each developmental stage exhibit distinctive functional characteristics with respect to the cell cycle, response to cytokines, proliferation potential, and long-term hematopoietic function 32,5254 . Accordingly, many hematopoietic functions, including myeloid and immune functions, become distinct across the fetal, neonatal and adult stages, which in turn become differentially vulnerable to hematological disorders such as bone marrow failure or hematological malignancies 5356 .…”
Section: Discussionmentioning
confidence: 99%
“…As the focus of this review is the role of sphingolipids in hematopoiesis, herein we have presented only a very simplified view of how hematopoiesis is currently understood; this is intended as a guide for the analysis summarized in the later sections. For an in-depth discussion of the processes that govern hematopoiesis, the reader is referred to the following excellent reviews [4,11,[13][14][15][16]].…”
Section: Introduction 1hematopoietic Lineage Commitmentmentioning
confidence: 99%